Author Correction: c-Met activation leads to the establishment of a TGFβ-receptor regulatory network in bladder cancer progression (Nature Communications, (2019), 10, 1, (4349), 10.1038/s41467-019-12241-2) - Sim, W.J.; Iyengar, P.V.; Lama, D.; Lui, S.K.L.; Ng, H.C.; Haviv-Shapira, L.; Domany, E.; Kappei, D.; Tan, T.Z.; Saei, A.; Jaynes, P.W.; Verma, C.S.; et al. (2019)
© 2019, The Author(s). The original version of this Article contained an error in the spelling of the author Azad Saei, which was incorrectly given as Azad Saie. This has now been corrected in both the PDF and HTML versions of the Article.